(untitled) (Bulletin KNOB, 2008)
The three large towns of Holland, Amsterdam, The Hague and Rotterdam, each had their own building trade by the end of the 18th century. The Amsterdam building trade was the largest and had much impact on the surrounding area. Amsterdam master builders were called in there and citizens of Amsterdam were in charge in the countryside. In The Hague it was particularly the administrative circles that were fond of representation, but their home grounds were far away, so that their buildings in the countryside did not resemble their houses in town. Rotterdam was a young town, surrounded by more important towns, such as Dordrecht, Delft and Gouda. It was not until the 17th century that it outgrew them, but it retained a primitive building trade with designing building contractors for a long time. Only for very special buildings was the service of a real architect from outside called in, who designed exclusively and supervised the execution. In such situations, Rotterdam and Gouda availed themselves of the services of The Hague architect Pieter de Swart. His death in 1773 paved the way for the young draughtsman of Italian descent, Carlo Giovanni Francesco Giudici (1746-1819). The energetic stone trader George Elgin from Scotland, who had settled in Rotterdam in 1754, must have discovered Giudici as draughtsman and assistant around 1770. Gradually Giudici also obtained a few commissions for the town and after 1778 a regular association with the Admiralty. Much of his work was lost, due to town extension and the bombing of Rotterdam in 1940. Especially the unexecuted designs are important, such as an entry for the competition for the Groningen Town Hall (1775) and a plan for the Rotterdam Town Hall (1781). These had been designed in a somewhat international style with a clear English slant to them, such as open columnal portico’s, horizontal wall bands between the floors, fanciful spires and tripartite division of glass panes in the windows. Only a few important works have been preserved outside Rotterdam, such as two large buildings in Schiedam and some buildings in Leiden after the gunpowder explosion of 1807. No Italian, nor French influence is to be recognized in his work.